The Mexican Drought Atlas: Tree-ring reconstructions of the soil moisture balance during the late pre-Hispanic, colonial, and modern eras. (1st October 2016) - Stahle, David W.; Cook, Edward R.; Burnette, Dorian J.; Villanueva, Jose; Cerano, Julian; Burns, Jordan N.; Griffin, Daniel; Cook, Benjamin I.; Acuña, Rodolfo; Torbenson, Max C.A.; Szejner, Paul; Howard, Ian M.
Abstract: Mexico has suffered a long history and prehistory of severe sustained drought. Drought over Mexico is modulated by ocean-atmospheric variability in the Atlantic and Pacific, raising the possibility for long-range seasonal climate forecasting, which could help mediate the economic and social impacts of future dry spells. The instrumental record of Mexican climate is very limited before 1920, but tree-ring chronologies developed from old-growth forests in Mexico can provide an excellent proxy representation of the spatial pattern and intensity of past moisture regimes useful for the analysis of climate dynamics and climate impacts. The Mexican Drought Atlas (MXDA) has been developed from an extensive network of 252 climate sensitive tree-ring chronologies in and near Mexico. The MXDA reconstructions extend from 1400 CE–2012 and were calibrated with the instrumental summer (JJA) self-calibrating Palmer Drought Severity Index (scPDSI) on a 0.5° latitude/longitude grid extending over land areas from 14 to 34°N and 75–120°W using Ensemble Point-by-Point Regression (EPPR) for the 1944–1984 period. The grid point reconstructions were validated for the period 1920–1943 against instrumental gridded scPDSI values based on the fewer weather station observations available during that interval. The MXDA provides a new spatial perspective on the historical impacts of moisture extremes over Mexico during the past 600-years, including the Aztec Drought of One Rabbit in 1454, the drought of El Año de Hambre in 1785–1786, and the drought that preceded the Mexican Revolution of 1909–1910. The El Niño/Southern Oscillation (ENSO) is the most important ocean-atmospheric forcing of moisture variability detected with the MXDA. In fact, the reconstructions suggest that the strongest central equatorial Pacific sea surface temperature (SST) teleconnection to the soil moisture balance over North America may reside in northern Mexico. This ENSO signal has stronger and more time-stable correlations than computed for either the Atlantic Multidecadal Oscillation or Pacific Decadal Oscillation. The extended Multivariate ENSO Index is most highly correlated with reconstructed scPDSI over northern Mexico, where warm events favor moist conditions during the winter, spring, and early summer. This ENSO teleconnection to northern Mexico has been strong over the past 150 years, but it has been comparatively weak and non-stationary in the MXDA over central and southern Mexico where eastern tropical Pacific and Caribbean/tropical Atlantic SSTs seem to be more important. The ENSO teleconnection to northern Mexico is weaker in the available instrumental PDSI, but analyses based on the millennium climate simulations with the Community Earth System Model suggest that the moisture balance during the winter, spring, and early summer over northern Mexico may indeed be particularly sensitive to ENSO forcing. Nationwide drought is predicted to become more common with anthropogenic climate change, but the MXDA reconstructions indicate that intense "All Mexico" droughts have been rare over the past 600 years and their frequency does not appear to have increased substantially in recent decades. Graphical abstract: The Mexican Drought Atlas uses 252 climate sensitive tree-ring chronologies to reconstruct the summer Palmer Drought Severity Index at 1501 0.5° latitude/longitude grid points over Mexico and adjacent land areas. Four severe droughts are depicted here, including three previously documented events (a, c, d) and the reconstructed drought that afflicted much of Mexico soon after Conquest (b). Highlights: The Mexican Drought Atlas (MXDA) provides reconstructed PDSI maps from 1400 to 2012. MXDA provides a detailed spatial perspective on severe droughts in Mexican history. ENSO is the strongest ocean-atmospheric forcing detected with the MXDA.